Identifying the epileptogenic zone by four non-invasive imaging techniques versus stereo-EEG in MRI-negative pre-surgery epilepsy patients. Issue 8 (August 2020) - Rossi Sebastiano, Davide; Tassi, Laura; Duran, Dunja; Visani, Elisa; Gozzo, Francesca; Cardinale, Francesco; Nobili, Lino; Del Sole, Angelo; Rubino, Annalisa; Dotta, Sara; Schiaffi, Elena; Garbelli, Rita; et al.
Highlights: Non-invasive techniques considered together reached an accuracy of 60–80% in identifying the epileptogenic zone (EZ) compared to SEEG. The diagnostic yield of non-invasive techniques increased in the subgroup of patients with EZ involving two or more lobes. EEG-fMRI, MEG or HR-EEG and PET appeared the best combination of techniques in the evaluation of multilobar EZ. Abstract: Objective: We evaluated four imaging techniques, i.e. Electroencephalography (EEG)-functional Magnetic Resonance Imaging (MRI) (EEG-fMRI), High-resolution EEG (HR-EEG), Magnetoencephalography (MEG) and 2-[18F]fluoro-2-deoxy-D-glucose positron emission tomography (PET), for the identification of the epileptogenic zone (EZ) in 41 patients with negative MRI, candidate to neurosurgery. Methods: For each technique, results were compared to the Stereo-EEG. Diagnostic measures were calculated with respect to the post-surgical outcome, either for all the patients (39/41, two patients excluded) and for the subgroup of patients with the EZ involving more than one lobe (20/41). Results: When considered individually, each functional technique showed accuracy values ranging 54, 6%–63, 2%, having PET, MEG and HR-EEG higher sensitivity, and EEG-fMRI higher specificity. In patients with multilobar epileptogenic zone, functional techniques achieved the best accuracies (up to 80%) when three techniques, including EEG-fMRI, were considered together. Conclusions: The study highlights the accuracy of a combination of functional imaging techniques in the identification of EZ in MRI negative focal epilepsy. The best diagnostic yield was obtained if the combination of PET, MEG (or HR-EEG as alternative), EEG-fMRI were considered together. Significance: The functional imaging techniques may improve the presurgical workup of MRI negative focal epilepsy, if epileptogenic zone involves more than one lobe.